How does scarcity uniquely inform the financial motives and outcomes of middle-class, non-retired households? - Lurtz, Meghaan R. (Kansas State University, 2019)
The 2016 Survey of Consumer Finances was used to investigate the impact of scarcity on the savings motives and debt of middle-class, non-retired households. This project adds to financial planning literature by incorporating previously unobserved variables, financial and time scarcity, in financial decision-making. Its use of the scarcity lens has also provided new insights for serving the middle-class with financial planning. Middle-class household decision-making was impacted by financial and time scarcity. Objective financial scarcity was related to increased odds of saving for basic needs and negatively related to saving for retirement. Objective financial scarcity was negatively associated with household debt, which can be attributed to credit constraints lenders want. Subjective financial scarcity was negatively associated with saving for retirement and at the same time positively associated with saving for esteem or luxury. Objective time scarcity was positively related to higher levels of household debt. Subjective time scarcity had a significant but mixed relationship with household debt. Financial planners and financial counselors working with the middle-class should consider the impact of scarcity for managing debt and shaping goals that will influence saving for retirement.
Keywords: Scarcity; Debt; Middle-class; Savings motives